Impact of Obesity and Hyperglycemia on Pregnancy-specific Urinary Incontinence - Vesentini, Giovana [UNESP]; Piculo, Fernanda [UNESP]; Marini, Gabriela [UNESP]; Barbosa, Angélica Mércia Pascon [UNESP]; Corrente, José Eduardo [UNESP]; Rudge, Marilza Vieira Cunha [UNESP] (Federação das Associações de Ginecologia e Obstetrícia, 2022)
Objective The lack of data on the impact of hyperglycemia and obesity on the prevalence of pregnancy-specific urinary incontinence (PSUI) led us to conduct a cross-sectional study on the prevalence and characteristics of PSUI using validated questionnaires and clinical data. Methods This cross-sectional study included 539 women with a gestational age of 34 weeks who visited a tertiary university hospital between 2015 and 2018. The main outcome measures were the prevalence of PSUI, the International Consultation on Incontinence Questionnaire Short Form (ICIQ-SF), and the Incontinence Severity Index (ISI) questionnaires. The women were classified into four groups: normoglycemic lean, normoglycemic obese, hyperglycemic lean, and hyperglycemic obese. The differences between groups were tested using descriptive statistics. Associations were estimated using logistic regression analysis and presented as unadjusted and adjusted odds ratios. Results Prevalence rates of PSUI were no different between groups. However, significant difference in hyperglycemic groups worse scores for severe and very severe PSUI. When adjusted data for confound factors was compared with normoglycemic lean group, the hyperglycemic obese group had significantly higher odds for severe and very severe forms of UI using ICIQ-SF (aOR 3.157; 95% CI 1.308 to 7.263) and ISI (aOR 20.324; 95% CI 2.265 to 182.329) questionnaires and highest perceived impact of PSUI (aOR 4.449; 95% CI 1.591 to 12.442). Conclusion Our data indicate that obesity and hyperglycemia during pregnancy significantly increase the odds of severe forms and perceived impact of PSUI. Therefore, further effective preventive and curative treatments are greatly needed.
Impacto da obesidade e hiperglicemia na incontinência Urinária específica da gravidez
Keywords: diabetes mellitus; maternal obesity; pregnancy; urinary incontinence